Clinical Use of DPP-4 Inhibitors - Gallwitz, Baptist (Frontiers in Endocrinology, 2019)
DPP-4 inhibitors were introduced for the treatment of type 2 diabetes in 2006. They stimulate insulin secretion and inhibit glucagon secretion by elevating endogenous GLP-1 concentrations without an intrinsic hypoglycaemia risk. Their efficacy potential to lower HbA1c is in the range between 0.5-1.0 % and their safety profile is favorable. DPP-4 inhibitors are body weight neutral and they have demonstrated cardiovascular safety. Most compounds can be used in impaired renal function. Guidelines suggest the additional use of DPP-4 inhibitors after metformin failure in patients that do not require antidiabetic therapy with proven cardiovascular benefit. Recently, DPP-4 inhibitors have increasingly replaced sulfonylureas as second line therapy after metformin failure and many metformin/DPP-4 inhibitor fixed dose combinations are available. In later stages of type 2 diabetes, DPP-4 inhibitors are also recommended in the guidelines in triple therapies with metformin and SGLT-2 inhibitors or with metformin and insulin. A treatment with DPP-4 inhibitors should be stopped, when GLP-1 receptor agonists are used. DPP-4 inhibitors can be used as monotherapy when metformin is contraindicated or not tolerated. Some studies have shown value of initial metformin-DPP-4 inhibitor combination therapy in special populations. This article gives an overview on the clinical use of DPP-4 inhibitors.